Managing Heart Failure with Preserved Ejection Fraction; A Short Review of Latest Evidences - Mahaseth, A.; Karki, P. (Kathmandu University Medical Journal, 2022)
Heart failure with preserved ejection fraction (HFpEF) is a clinical dilemma and various clinical trials so far have failed to give a concrete evidence of reducing mortality and major adverse cardiac events (MACE) in this condition. A detailed analysis of the existing evidences and a future plan for a concrete trial design with long duration of follow up is needed to address the dilemma of Heart failure with preserved ejection fraction. The objective of this short review was to review the latest and major randomized controlled trials and study the primary outcomes. The public database of PubMed, Google Scholar and Cochrane were extensively searched for all randomized controlled trials using keywords of Heart failure with preserved ejection fraction, major adverse cardiac events, Hospitalizations; and studies were included in the review if data were reported for patients with ejection fraction > 40%, did not include congenital heart disease, and demonstrated evidence of diastolic failure on echocardiogram (ECHO), and evaluated hospitalizations, major adverse cardiac events and cardiovascular mortality. Despite the major trials reporting improved primary composite endpoints with newer drugs the results have to be interpreted cautiously since the primary outcome were mostly driven by heart failure hospitalizations and not mortality reduction.